Prognostic value of Siglec-15 expression in patients with solid tumors: A meta-analysis - Jiang, Kui-Ying; Qi, Li-Li; Liu, Xin-Bo; Wang, Yong; Wang, Ling (Frontiers in Oncology, 2023)
Background: Siglec-15 is expressed in a variety of cancers. However, the role of Siglec-15 in the prognosis of cancer patients remains controversial. Therefore, we conducted a meta-analysis to clarify the potential prognostic value of Siglec-15 in solid tumors. Methods: The PubMed, Web of Science, Embase and CNKI databases were comprehensively searched to identify studies assessing the effect of Siglec-15 on the survival of cancer patients. Hazard ratios (HRs) with 95% confidence intervals (CIs) for overall survival (OS), progression-free survival (PFS) and disease-specific survival (DSS) from individual studies were evaluated. Results: The data from 12 observational studies consisting of 1285 patients were summarized. Elevated baseline Siglec-15 expression was significantly correlated with poor OS (pooled HR = 1.31, 95% CI: 1.06–1.62; P = 0.012). However, high Siglec-15 expression predicted a significantly better DSS (pooled HR = 0.71, 95% CI: 0.51–0.99; P = 0.046) but not PFS (pooled HR = 1.49, 95% CI: 0.46–4.87; P=0.510). In addition, high Siglec-15 expression was not associated with PD-L1 (OR=1.07, 95% CI: 0.23–4.94; P = 0.936). High Siglec-15 expression was associated with male sex (OR = 1.408, 95% CI: 1.044-1.898; P = 0.025), larger tumor size (OR = 2.009, 95% CI: 1.274-3.168; P = 0.003), and advanced tumor-node-metastasis (TNM) stage (OR = 1.837; 95% CI: 1.187-2.843; P =0.006) in solid tumors. Conclusions: This updated study suggested the expression of Siglec-15 is significantly associated with poor outcomes in human solid tumors, but further studies are needed to determine the prognostic value of Siglec-15 in solid tumors.